ANALISIS MATERI AKIDAH AKHLAK DALAM UPAYA MENGHINDARI FAHAM RADIKALISME PADA PARA PESERTA DIDIK MADRASAH ALIYAH - Nurulhaq, Dadan (Atthulab: Islamic Religion Teaching and Learning Journal, 2016)
Religious radicalism occurred due to the understanding of the faith that is not true, because faith is not really going to lead to a blind fanatic behavior, impose his will and being loud and rude. While true faith will lead to right behavior. Creed became especially on the matter at the madrasah madrasahaliyah. Based on the analysis of the material on the creed of madrasah aliyah that have different backgrounds such as NahdlatulUlama (NU), Muhammadiyah and Persis that there is the same concept of the urgency of the true faith and creed learning efforts that will result in learners madrasah aliyah for blind fanatics, tough and rough. Although it furu'iyah they have all kinds of differences, but for the affairs of the same creed is based on the belief ahlussunnahwalJama'ah. Analysis of the material MA moral theology is necessary to fortify the faith of the students with the correct creed that is not easily influenced by creeds that actually mislead them and afflict the lives of the people of Indonesia. This research method using qualitative methods were trying to find the details about the curriculum of moral theology at three study sites. Results of this study found that the condition of moral theology curriculum at three study sites is referring to the curriculum of religious ministry RI to plus materials typical of the three study sites. The efforts made on the three research sites in avoiding radicalism is through learning that does not make learners fanatic and violent.